Clinicopathologic Spectrum of Gastrointestinal T-cell Lymphoma: Reappraisal Based on T-cell Receptor Immunophenotypes. (June 2016) - Tanaka, Tsutomu; Yamamoto, Hideko; Elsayed, Ahmed Ali; Satou, Akira; Asano, Naoko; Kohno, Kei; Kinoshita, Tomohiro; Niwa, Yasumasa; Goto, Hidemi; Nakamura, Shigeo; Kato, Seiichi
Abstract : The differential diagnosis of primary gastrointestinal EBV − T-cell lymphoma (GITCL) includes enteropathy-associated T-cell lymphoma (EATL), peripheral T-cell lymphoma, not otherwise specified, adult T-cell leukemia/lymphoma, and anaplastic large cell lymphoma. Type II EATL is considered to be a tumor of intraepithelial lymphocytes. However, the evaluation of intraepithelial lymphocytosis by biopsy specimens is challenging, which poses a diagnostic problem between the EATL and peripheral T-cell lymphoma, not otherwise specified. This situation requested us to establish a pragmatic diagnostic approach for the classification of GITCL. We identified 42 cases of GITCL and analyzed clinicopathologic features, especially addressing their T-cell receptor (TCR) phenotype. Nine (21%) of 42 GITCL cases were positive for TCRγ protein expression. Among these TCRγ + cases, TCRβ expression or not was detected in 5 and 4, respectively, but resulted in no further clinicopathologic differences. TCRβ positivity without TCRγ expression (β + γ − ) was seen in 9 GITCL patients (21%). Twenty-four patients (57%) were negative for TCRβ and γ expression (β − γ − ). Compared with TCRβ + γ − or β − γ − type, TCRγ + cases were characterized by exclusive involvement of intestinal sites (100% vs. 11%, P <0.001; 100% vs. 58%, P =0.032, respectively), but not of stomach (0% vs. 78%, P =0.002; 0% vs. 38%, P =0.039, respectively). Notably, TCRγ positivity was an independent unfavorable prognostic factor among our GITCL patients ( P <0.001). Considering our results, TCRγ + GITCL, that is, intestinal γδ T-cell lymphoma, appears to constitute a distinct disease entity. Abstract : Supplemental Digital Content is available in the text.